STRATEGIES OF WOMEN FARMERS IN ACHIEVING FAMILY SECURITY: A CASE STUDY OF BANDUNG JAYA VILLAGE, KEPAHIANG - Panji Suminar; Ika Pasca Himawati; Jimmy Jimmy Yogari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study analyzes the strategies employed by women farmers in achieving family food security in Bandung Jaya Village, Kabawetan District, Kepahiang Regency. Using a qualitative case study design, eight purposively selected informants including members of the “Kaba Indah Lestari” Women Farmers Group (KWT) and village authorities were interviewed through in-depth interviews supported by non-participant observations and document analysis. The findings reveal four integrated strategies: (1) food production through optimal and sustainable use of family fields, group plots, and home gardens; (2) food access strategies involving produce exchange, selective selling to middlemen, and livelihood diversification; (3) food management and consumption strategies that ensure balanced household nutrition through storage, processing, and adaptive menu planning; and (4) empowerment through KWT as a platform for capacity building, knowledge exchange, and social solidarity. Using Moser’s Gender and Development (GAD) framework, the study shows that women farmers perform productive, reproductive, and community management roles that are essential for strengthening household resilience and sustaining local food systems. The study concludes that women’s empowerment plays a critical role in building a gender-equitable and sustainable food security system in rural communities.